2018
DOI: 10.7150/jbji.22566
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Risk Factors for Polymicrobial Posttraumatic Osteomyelitis

Abstract: Background: We hypothesized that polymicrobial posttraumatic osteomyelitis (PTO) may be associated with worse outcomes when compared to monomicrobial PTO. We therefore attempted to show the outcomes and predisposing factors associated with polymicrobial PTO.Methods: A single-center case-control study was carried out from 2007 to 2012. The outcome variables analyzed were: the need for additional surgical and antibiotic treatments, rates of amputation, and mortality associated with the infection. Univariate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 25 publications
4
21
2
Order By: Relevance
“…Thus, infected nonunions can be compared to posttraumatic osteomyelitis being a chronic bone infection as well. Jorge et al reported 37.8% polymicrobial infections using standard culturing techniques in posttraumatic osteomyelitis [12]. Wimmer and co-workers reported 46.6% polymicrobial infections in PJI [8], while Bozhkova et al found 28.5% PJIs to be polymicrobial [13].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, infected nonunions can be compared to posttraumatic osteomyelitis being a chronic bone infection as well. Jorge et al reported 37.8% polymicrobial infections using standard culturing techniques in posttraumatic osteomyelitis [12]. Wimmer and co-workers reported 46.6% polymicrobial infections in PJI [8], while Bozhkova et al found 28.5% PJIs to be polymicrobial [13].…”
Section: Discussionmentioning
confidence: 99%
“…Multispecies biofilm-like communities are responsible for causing persistent infections in a wide range of body sites, including the lung (24)(25)(26)(27)(28)(29)(30)(31), oral cavity (32,33), middle ear (34)(35)(36), urinary tract (37)(38)(39), and both surgical and chronic wounds (40)(41)(42)(43)(44)(45). In several disease settings, polymicrobial infections have been reported to cause worse outcomes than single-species infections (46)(47)(48)(49)(50)(51)(52)(53)(54). In particular, polymicrobial bloodstream infections are associated with higher rates of mortality than monospecies infections (46)(47)(48)(49)(50).…”
Section: The Etiology Of Most Chronic Infections Is Polymicrobialmentioning
confidence: 99%
“…In fact, commensal species with distinct agr types have the ability to attenuate virulence in pathogenic species when co-colonizing mucosal surfaces, thereby protecting the host from S. aureus virulence factors regulated by Agr [103,104]. Polymicrobial S. aureus infections are frequently characterized in post-traumatic osteomyelitis and are associated with more severe patient outcomes [105]. In other disease models, co-infecting bacterial species, including Pseudomonas aeruginosa, augment S. aureus agr expression [106].…”
Section: Regulatory Control Of Aip Is Strain and Species Specificmentioning
confidence: 99%